2020
DOI: 10.1590/0103-8478cr20190382
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and antioxidant enzyme activity in seedlings of diploid and tetraploid bahiagrass under water restriction

Abstract: The objective of the following research was to investigate the physiological responses of two bahiagrass genotypes (Paspalum notatum Flügge) submitted to water restriction, induced by polyethylene glycol (PEG6000), during seed germination. Seeds of cv. Pensacola (diploid) and Bagual ecotype (tetraploid) were placed on paper moistened with osmotic solutions at potentials of 0.0; -0.1; -0.2 and -0.3 MPa. Composed of two subsamples of 100 seeds and four experimental units per treatment, the germination test was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Different kinds of enzymes can effectively minimize the deleterious effects of ROS in different ways; therefore, antioxidant enzymes are considered crucial indicators for evaluating plant stress tolerance [ 71 , 72 ]. In studies on stress resistance in plants, polyploids showed a more efficient resistant system than diploids [ 73 ]. Moreover, the increased tolerance to environmental stress of polyploids was attributed to their higher antioxidant enzyme activity to a large extent [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of enzymes can effectively minimize the deleterious effects of ROS in different ways; therefore, antioxidant enzymes are considered crucial indicators for evaluating plant stress tolerance [ 71 , 72 ]. In studies on stress resistance in plants, polyploids showed a more efficient resistant system than diploids [ 73 ]. Moreover, the increased tolerance to environmental stress of polyploids was attributed to their higher antioxidant enzyme activity to a large extent [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%